Adaptation and Concurrent Validity of Screen for Children Anxiety Related Emotional Disorders (SCARED) - Shaf Ahmed; Tamkeen Ashraf Malik; Amna Naveed (NUST Journal of Social Sciences and Humanities)
The current study was designed to adapt and investigate the psychometric properties of SCARED (screening children for anxiety related emotional disorders) as the first anxiety related emotional disorder screening tool for Pakistani children. The sample consisted of 8 to 11-year-old (N=322, mean age= 9.48) primary class children, including 157 girls and 165 boys. The 41-item child version of SCARED was translated into Urdu language by following Brislin’s translation method. The convergent validity of this scale was determined by comparing it with DBDRS (Disruptive Behaviour Disorder Rating Scale). Cronbach’s alpha reliability of SCARED scale was 0.89 and its subscales demonstrated internal consistencies ranging from 0.68 to 0.76 i.e. moderate to high, except one subscale SH, 0.45. The total score of SCARED was positively correlated with conduct disorders (r= 0.16, p <0.01), inattentive (r= 0.19, p < 0.01), hyper impulsive (r= 0.16, p < 0.01) and with ODD (r= 0.16, p < 0.01).Furthermore, the chi square result showed statistically non-significant association between cases and non-cases of SCARED and cases and non-cases of all subscales of DBDRS including conduct disorders (χ2= 2.45, p> 0.05), inattention(χ2= 0.11, p > 0.05), hyperactivity/ impulsive(χ2= 0.23, p > 0.05), ODD (χ2= 0.05, p > 0.05) and with ADHD combined scores (χ2= 0.27, p > 0.05.The findings supported convergent validity for anxiety disorders with disruptive behaviours depicting the comorbidity of anxiety and disruptive behaviour. The study provides support for the convergent validity of SCARED with DBDRS.